A multi- case study of five female urban superintendents: perceptions of leadership, change, and challenges - Stroh, Jeanne L. (Kansas State University, 2012)
Urban school leaders, particularly superintendents are on the frontlines for raising student achievement at all levels. The work of urban superintendents is intensive given the challenges they encounter. Research has indicated that school leaders who possess and enact skills and knowledge that support change leadership. The question, then, is this: what patterns and themes exist in the use of those attributes by female urban superintendents, to support systemic changes in their school districts. This researcher chose to look at these attributes through the lens of female urban superintendents who were members of the Council of Great City Schools, who had at least three years tenure in the district, and who had realized increased student achievement during their tenure. This study identified and described through case studies the attributes that emerged from the data. Each of the five participants were interviewed twice with questions based on the leadership attributes Reeves (2007) described, the change attributes Fullan (2009) and Knoster, Villa and Thousand (2000) identified, and the superintendent challenges described by the Texas Education Agency (2007). In addition to the interviews, biographies and vitas were collected. Other artifacts such as news articles, television interviews, district newsletters, and district websites were also reviewed. The study revealed that there were patterns and themes that emerged based on the leadership and change attributes, and the challenges urban female superintendents encountered. The leadership attributes defined by Reeves (2007) were: communication, vision, relationships, building capacity in others, access the expertise of others, and decision making. The change attributes defined by Fullan (2009) and Knoster, Villa and Thousand (2000) were: vision, skills, incentives, resources, and action plan. The implications of this study revealed that below the surface of these important attributes and challenges lay social justice issues that may first need to be addressed.
Keywords: Female urban superintendents; Educational leadership (0449)